Peran Pendidikan Islam Multikultural dalam Membangun Toleransi di Sekolah dan Madrasah - Rayhan Mardatillah; Fery Diantoro; Azizah Dwi Wulandari; Helda Anisa Putri Wulandari (AJER: Advanced Journal of Education and Religion, 2026)
This research is motivated by the persistence of intolerance in schools and Islamic schools, indicating the suboptimal role of Islamic education in fostering tolerant character. This study aims to analyze the role of multicultural Islamic education, identify factors influencing its success, and formulate strategies for its implementation in fostering tolerance. The study employed a library research method, reviewing relevant books and scientific articles. Data were analyzed descriptively and qualitatively through the stages of reduction, classification, and interpretation. The results indicate that multicultural Islamic education plays a significant role in instilling values of tolerance through the integration of justice, equality, and respect for differences in learning. Successful implementation is influenced by teacher competence, an inclusive curriculum, and a supportive school environment. Conversely, time constraints, low teacher understanding, and a lack of clear policies are key challenges. Effective strategies include the implementation of dialogic learning, the use of participatory methods, and strengthening teacher role models. These findings confirm that multicultural Islamic education is capable of developing tolerant and inclusive students